Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Should I Stay or Should I Go? Discussing the Advantages and Disadvantages of Taking a Gap Year - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Virtual Employees in India: Off-site Employment for Large Corporations. Two oral exams - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Modern Slavery vs. Fairtrade: Raising Awareness of the Working Conditions in India - Bauer, Maike; Menschig, Leigh (Englisch Betrifft Uns)

Diaspora Short Stories – A Meaningful Aspect in Young Adult Literature? - Bauer, Maike

Computing generalizations of temporal ϵL concepts with next and global - Tirtarasa, Satyadharma; Turhan, Anni-Yasmin (SAC ’22: The 37th {ACM/SIGAPP} Symposium on Applied Computing, Virtual Event, April 25 - 29, 2022)

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts (GDSU) vom 09. bis 12.03.2022 in Köln - Janicki, Nicole

Efficient TBox Reasoning with Value Restrictions using the Flower Reasoner - Baader, Franz; Koopmann, Patrick; Michel, Friedrich; Turhan, Anni-Yasmin; Zarrieß, Benjamin (Theory Pract. Log. Program.)

Gott wird Mensch. Weihnachten zwischen Fiktion und Evangelium - Janus, Richard

Smart cities and smart governance models for future cities - Nastjuk, I.; Trang, Simon Thanh-Nam; Papageorgiou, E. (Electronic Markets)

What to do after a data breach? Examining apology and compensation as response strategies for health service providers - Masuch, K.; Greve, M.; Trang, Simon Thanh-Nam (Electronic Markets)

Apologize or Justify? Examining the Impact of Data Breach Response Actions on Stock Value of Affected Companies - Masuch, K.; Greve, M.; Trang, Simon Thanh-Nam (Computers & Security)

REBench: Microbenchmarking Framework for Relation Extraction Systems - Manzoor, Ali; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web – ISWC 2022)

Parameterised complexity of model checking and satisfiability in propositional dependence logic - Mahmood, Yasir; Meier, Arne (Annals of Mathematics and Artificial Intelligence)
Abstract Dependence Logic was introduced by Jouko Väänänen in 2007. We study a propositional variant of this logic (PDL) and investigate a variety of parameterisations with respect to central decision problems. The model checking problem (MC) of PDL is NP -complete (Ebbing and Lohmann, SOFSEM 2012). The subject of this research is to identify a list of parameterisations (formula-size, formula-depth, treewidth, team-size, number of variables) under which MC becomes fixed-parameter tractable. Furthermore, we show that the number of disjunctions or the arity of dependence atoms (dep-arity) as a parameter both yield a paraNP-completeness result. Then, we consider the satisfiability problem (SAT) which classically is known to be NP -complete as well (Lohmann and Vollmer, Studia Logica 2013). There we are presenting a different picture: under team-size, or dep-arity SAT is paraNP -complete whereas under all other mentioned parameters the problem is FPT . Finally, we introduce a variant of the satisfiability problem, asking for a team of a given size, and show for this problem an almost complete picture.
Keywords: Applied Mathematics; Artificial Intelligence

A parameterized view on the complexity of dependence and independence logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Journal of Logic and Computation)
Abstract In this paper, we investigate the parameterized complexity of model checking for Dependence and Independence logic, which are well studied logics in the area of Team Semantics. We start with a list of nine immediate parameterizations for this problem, namely the number of disjunctions (i.e. splits)/(free) variables/universal quantifiers, formula-size, the tree-width of the Gaifman graph of the input structure, the size of the universe/team and the arity of dependence atoms. We present a comprehensive picture of the parameterized complexity of model checking and obtain a division of the problem into tractable and various intractable degrees. Furthermore, we also consider the complexity of the most important variants (data and expression complexity) of the model checking problem by fixing parts of the input.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

If You Can’t Get Them to the Lab: Evaluating a Virtual Study Environment with Security Information Workers - Huaman, Nicolas; Krause, Alexander; Wermke, Dominik; Klemmer, Jan H.; Stransky, Christian; Acar, Yasemin; Fahl, Sascha (Eighteenth Symposium on Usable Privacy and Security, SOUPS 2022, Boston, MA, USA, August 7-9, 2022)

“They’re not that hard to mitigate”: What Cryptographic Library Developers Think About Timing Attacks - Jancar, Jan; Fourné, Marcel; Braga, Daniel De Almeida; Sabt, Mohamed; Schwabe, Peter; Barthe, Gilles; Fouque, Pierre-Alain; Acar, Yasemin (2022 IEEE Symposium on Security and Privacy (SP))

How Does Usable Security (Not) End Up in Software Products? Results From a Qualitative Interview Study - Gutfleisch, Marco; Klemmer, Jan H.; Busch, Niklas; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

27 Years and 81 Million Opportunities Later: Investigating the Use of Email Encryption for an Entire University - Stransky, Christian; Wiese, Oliver; Roth, Volker; Acar, Yasemin; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)